2018
DOI: 10.20862/0042-4676-2018-99-5-244-252
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion and Neurotropic Single-Photon Emission Computed Tomography Features in Patients With Primary Pulmonary Hypertension

Abstract: Objective.To compare cardiac123I-MIBG and99m Tc-MIBI single-photon emission computed tomography (SPECT) data in patients with primary pulmonary hypertension (PPH).Material and methods.The study included 22 patients with confirmed diagnosis of PPH, with clinical status assessment, Holter ECG monitoring and rest cardiac ultrasound (US) data. All patients, as well as a group of healthy volunteers (n=20) underwent myocardial perfusion SPECT with99mTc-MIBI at rest and after treadmill exercise test, and myocardial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Анализируя накопление 123 I-МИБГ в предсердиях, представляется возможным локализовать области повышенной симпатической активности, что позволяет провести эффективную радиочастотную аблацию у пациентов с фибрилляцией предсердий [37]. Нарушение накопления 123 I-МИБГ в миокарде продемонстрировало тесную связь с тяжестью гипертрофической кардиомиопатии [38] и идиопатической легочной гипертензии [39].…”
Section: радионуклидная равновесная вентрикулографияunclassified
“…Анализируя накопление 123 I-МИБГ в предсердиях, представляется возможным локализовать области повышенной симпатической активности, что позволяет провести эффективную радиочастотную аблацию у пациентов с фибрилляцией предсердий [37]. Нарушение накопления 123 I-МИБГ в миокарде продемонстрировало тесную связь с тяжестью гипертрофической кардиомиопатии [38] и идиопатической легочной гипертензии [39].…”
Section: радионуклидная равновесная вентрикулографияunclassified
“…Over the past decade, a large number of papers have been published in which the problem of attenuation correction was discussed and contradictory conclusions were obtained. Some clinical researches have shown that AC has resulted in improved diagnostic accuracy over uncorrected images [7][8][9], while in others, only a slight improvement or no improvement was mentioned [10]. In some patient studies, AC images may have a significant decrease of apical intensity as shown in figure 1.…”
Section: Introductionmentioning
confidence: 99%